Use of Dexmedetomidine in a Parturient With Multiple Endocrine Neoplasia Type 2A Undergoing Adrenalectomy and Thyroidectomy: A Case Report. Issue 5 (1st March 2019) - Faulkner, Amanda L.; Swanson, Eric; McLarney, Thomas L.; Lee, Cortney Y.; Rebel, Annette
Abstract : Dexmedetomidine is a selective α2-agonist, frequently used in perioperative medicine as anesthesia adjunct. The medication carries a Food and Drug Administration pregnancy category C designation and is therefore rarely used for parturients undergoing nonobstetric surgery. We are reporting the use of dexmedetomidine in the anesthetic management of a parturient undergoing minimally invasive unilateral adrenalectomy for pheochromocytoma during the second trimester of pregnancy. Additionally, because of the multiple endocrine neoplasia type 2A constellation with diagnosis of medullary thyroid cancer, the patient underwent a total thyroidectomy 1 week after the adrenalectomy.